Wounds produced by firearm projectiles - Goller, Wolfgang; Castiglioni, Juan C; Bergalli, Luis A; Saccone, Rodolfo (Cirugía del Uruguay, 1973)
During the last 2 years, the surgeons· of the S. S. Army Hospital have operated 31 patients with vascular gun wounds. This paper offers an analysis on the balistic data, in order to explain sone arterial lesions. The importance of the temporary cavity made by the circumference of ali the thact sorrounding ali the way of the bullet through the tissues, which are radially moved son indirectally damaging vessels that never were. in contact with the bullet. The types of these wounds are enumerated. The isolated arterial spams, froftently coexisting with intima! injuries, even very small, favorable to secondary thrombosis, is noted for its infrequency. The paper insists on emergency surgery in beating haematomes and traumatic arterio-venous fistulae. Diagnosis and treatment of arterial injuries are systematized by the clinic and contrast radiologic study. I·he general therapeutic of arterial injuries, isolated or combined to neighbouring lesions, or associated to bone f which often complicates the evolution of these patients. Queremos expresar nuestro agradecimiento al Profesor Adj. Dr. Gonzalo Fernández que nos proporcionó estos datos balísticos